Z for Zachariah - O'Brien, Robert C. (Heinemann Educational Books Ltd, 1975)
A sixteen-year-old girl keeps her diary after a nuclear explosion has devastated the country. She thinks she is the only person left alive, until a man arrives in her valley. Her initial joy is replaced by fear and an instinct to survive - how can she be sure he will be friendly, in a world where everything has changed?...
Keywords: Juvenile Fiction / Adventure